The Mental Health of The Main Character in The Film "A Man Called Otto" - Rompas, Alfa Victory; Andries, Fivy; Rorimpandey, Rinny S (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
In today's life, lots of people are dealing with mental health problems, from small problems to ones that affect how they act and how others see them. Depression, anxiety, and sadness are something almost everyone goes through, causing problems like trouble sleeping, eating issues, feeling uncomfortable, or losing interest in things they used to enjoy. This study aims to explore mental health issues experienced by the main character, Otto Anderson, in the film "A Man Called Otto". The writer used qualitative research to gather data for this study, focusing on words and dialogue quotations from the film, as well as various supporting sources. Through a psychological approach, the writer examines the mental health issues and related problems depicted in the film, particularly those affecting the main character. The psychological theory used in this research is from Sigmund Freud’s theory which studies The Id, The Ego, and The Superego. The writer also analyzes the cause and effect of mental health in the film and finds the result that there are; Depression, Suicidal Thoughts, Irritability, and Unsocialized.